SPEED FLOW RELATIONSHIP IN BANDUNG URBAN AREA - A.A.Nusrihardono, Bambang
This study attempted to obtain the relationship between speed and flow in urban Bandung based on the general hypothesis that the speed decreases as the flow increases. The survey was conducted on 5 links of road in Bandung city used by various types of vehicles. Special reference was made to paratransit vehicles (minicab and bemo) of which there were a great different types of paratransit vehicles were also considered and their effects on the speed-flow relationship.To show the effect of the width of carriage way on the speed-flow relationship, the location for each survey was selected on links of road which had different widths of carriageway.The equation of the speed-flow relationship was derived by the regression method, using the computer.The intervals of observation for speed-flow data collection were 10 minutes and 1 minute and a discussion is made of the results obtained from the different intervals of observation.Using the obtained equation of speed-flow relationship, an attempt was made to consider and relate the other variables such as the speed-density and the flow-density relationship using the equation Q = D V from traffic flow theory.The obtained speed-flow relationship shows that the speed decreases as the flow incrases in a straight.